2014
DOI: 10.1371/journal.pone.0100655
|View full text |Cite
|
Sign up to set email alerts
|

Archform Comparisons between Skeletal Class II and III Malocclusions

Abstract: The purpose of this cross-sectional research was to explore the relationship of the mandibular dental and basal bone archforms between severe Skeletal Class II (SC2) and Skeletal Class III (SC3) malocclusions. We also compared intercanine and intermolar widths in these two malocclusion types. Thirty-three virtual pretreatment mandibular models (Skeletal Class III group) and Thirty-five Skeletal Class II group pretreatment models were created with a laser scanning system. FA (the midpoint of the facial axis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
(32 reference statements)
0
9
0
2
Order By: Relevance
“…From literature, it has been observed that significant changes in dental arch dimensions are associated with development of the permanent dentition from the age of 6 years (first molar) to 12 years (second molar) and finally 18 years (third molar) [ 9 – 12 ]. It is also important to note that the dental arch dimensions will also tend to differ between different participants of Angles classification [ 22 , 23 ], this is an additional source of variation that must be taken care of in such a study. So in this study, while we only included participants of Angles class I, it is possible that we may have missed the majority of changes in dental arch dimensions given our older study population, older than the mixed dentition.…”
Section: Discussionmentioning
confidence: 99%
“…From literature, it has been observed that significant changes in dental arch dimensions are associated with development of the permanent dentition from the age of 6 years (first molar) to 12 years (second molar) and finally 18 years (third molar) [ 9 – 12 ]. It is also important to note that the dental arch dimensions will also tend to differ between different participants of Angles classification [ 22 , 23 ], this is an additional source of variation that must be taken care of in such a study. So in this study, while we only included participants of Angles class I, it is possible that we may have missed the majority of changes in dental arch dimensions given our older study population, older than the mixed dentition.…”
Section: Discussionmentioning
confidence: 99%
“…This diversity has led some authors to recommend specific concepts for customizing the shape of dental arches for patients in order to improve the prospects of post-treatment stability, health, function, and appearance. 4 - 7 …”
Section: Discussionmentioning
confidence: 99%
“… 1 - 3 Because of the wide variety in dental arch forms between individuals, it is important to seek universal points of reference that could establish a guideline for individualizing arch forms for patients seeking orthodontic treatment. 2 , 4 It has been suggested to use the buccal aspect of mandibular alveolar bone, known as the WALA ridge, as such a reference. The WALA ridge is clinically identifiable as a soft-tissue band immediately superior to the mucogingival junction.…”
Section: Introductionmentioning
confidence: 99%
“…1 Until now, most research on the dental arch form has concerned arch form at the level of the crowns of the teeth (crown arch form) or basal bone arch form; studies on the root apex arch form have been very rare. [2][3][4][5] Recent progress in conebeam computed tomography (CBCT) has made root apex studies possible in living individuals. 6 The research considering crown arch forms includes the use of facial axis points (FA); the research considering the basal bone arch form includes the use of mucogingival junction points or root centre points.…”
Section: Introductionmentioning
confidence: 99%
“…6 The research considering crown arch forms includes the use of facial axis points (FA); the research considering the basal bone arch form includes the use of mucogingival junction points or root centre points. [2][3][4][5] However, the arch form constructed from these points is measured from two-dimensional models. As the positions of root apices are three-dimensional, root apex points should be measured three-dimensionally and projected onto the reference plane (eg, palatal plane, occlusal plane) to construct the arch form accurately.…”
Section: Introductionmentioning
confidence: 99%